STRATEGI PENYEDIAAN BENIH KEDELAI ANTAR LAPANG DAN ANTAR MUSIM DI BALAI BENIH TANAMAN PANGAN ACEH - Maimun Maimun; Romano Romano; Ismayani Ismayani (Universitas Teuku Umar, 2017)
seeds can produce soybean crops if followed by good agronomic treatment. This study aims to understand the strategy; Food Crops Hall encourages inter-field seed systems between seasons; And regulates the distribution of certified, evenly distributed seeds between field and inter-season for all of Aceh.. The results showed that proram of soybean seed tissue between field of atar season has not been consistently done in three development areas. Seed production capability for seed supply in three areas above average is only 27.6 percent of the seed requirement in accordance with the target and realization of planting in 2012 until 2016. The results of this study using the network of seeds between field and inter-season in the year 2015 only 32 tons which is intended for the location of stabilization production of 640 Ha in Kab. Pidie, Pidie Jaya and Kab.East Aceh. Jabalsim of soybean seeds in Aceh is small (27.6%) has met the needs of inter-season seeds, but has not been able to distribute on time inter-field. The pattern of production of jabalsim soybean seeds in Field 1 of 93.5 percent has followed the soybean cropping pattern, so as to meet the needs of soybean seeds in this region. In contrast to the production patterns of Fild 2 and Fild 3, only 6.5 percent of the seed needs are met, the shortage is imported from outside the region.